1994
DOI: 10.1002/sca.4950160312
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon and guided optical wave microscopies

Abstract: This article summarizes some recent developments in the field of surface plasmon and guided optical wave microscopies. It is shown that these imaging techniques based on evanescent light allow for a quantitative optical characterization of ultrathin films with a thickness sensitivity of a few Ångstroms and a lateral resolution of µm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 23 publications
0
46
0
Order By: Relevance
“…The measured reflectivity scans were compared with calculations for a model layer system by using the transfer matrix algorithm, based upon Fresnel's equations 1) . The variables in Fresnel's equations are the layer thickness and the dielectric constants of the materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured reflectivity scans were compared with calculations for a model layer system by using the transfer matrix algorithm, based upon Fresnel's equations 1) . The variables in Fresnel's equations are the layer thickness and the dielectric constants of the materials.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it has been demonstrated that surface plasmon spectroscopy or waveguide spectroscopy are well suited to analyse thin 1,2) and thick 2,3) polymer films. Experiments have been reported with variable sample temperatures T in order to identify, e. g., the thickness dependence of the glass transition temperature T g of ultrathin PMMA layers 4) .…”
Section: Introductionmentioning
confidence: 99%
“…The SPR setup was obtained from Resonant Probes (Goslar, Germany) (51). The sample cell is mounted on top of a -2 goniometer with the detector measuring the reflectivity changes as a function of the angle of incidence of the p-polarized incoming laser beam.…”
Section: Preparation Of the Metal Complex Of L With Cu(ii) And Ni(ii)mentioning
confidence: 99%
“…Surface plasmon resonance has become an important technique in the area of biosensor research (17)(18)(19). In SPR measurements, a gold surface is needed as the substrate to allow the excitation of surface plasmons (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%